4+5=-55-6x

Simple and best practice solution for 4+5=-55-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+5=-55-6x equation:


Simplifying
4 + 5 = -55 + -6x

Combine like terms: 4 + 5 = 9
9 = -55 + -6x

Solving
9 = -55 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
9 + 6x = -55 + -6x + 6x

Combine like terms: -6x + 6x = 0
9 + 6x = -55 + 0
9 + 6x = -55

Add '-9' to each side of the equation.
9 + -9 + 6x = -55 + -9

Combine like terms: 9 + -9 = 0
0 + 6x = -55 + -9
6x = -55 + -9

Combine like terms: -55 + -9 = -64
6x = -64

Divide each side by '6'.
x = -10.66666667

Simplifying
x = -10.66666667

See similar equations:

| x-9=-6x+19 | | 12x+7x=-5 | | -4(3-6D)=2(3d-8) | | 25a^2+2a=5868 | | 3x-10=-22+4x | | 2x+20=92 | | 13a+9b=13750 | | 9x=10+3x | | 13a+9b=13 | | x+3.1=1.6 | | x+.1=1.6 | | -x+3=-45+5x | | a^2+a=25 | | 7-2x=-4+23 | | y=100+75 | | 2a^2-16ab+14b^2=0 | | 40x+8(1.5)=525 | | (x-(2-5i))(x-(2+5i))=0 | | 4x-2-5x=-7 | | 81+256=625 | | 3-6x=3x-2x-46 | | 0.000579a^2-a+286.25=0 | | 6-5n=n+9 | | p+7=1.1 | | -7/8x-1/2=3/16x+5 | | 1x+2x+3x=82 | | 18+32=50 | | -(7x^3+2x^2-3)+(5x^2-30)= | | -6=2x-5x+3 | | 35x^2+21x= | | 5(6t-3)=6(3t-1) | | 2x+y(0.4+0.1)=5 |

Equations solver categories